Targeted imaging using ultrasound contrast agents. - Bloch, S.H.
The applications of ultrasound contrast agents have recently expanded from blood pool enhancement to include passive targeting of physiological systems (in particular, the lymphatic and reticuloendothelial systems) and molecular imaging of factors expressed in angiogenesis, atherosclerosis, and inflammation. This article summarizes the progress made in targeted imaging using ultrasound with an emphasis on the opportunities this research provides for both clinical and research applications. We begin with a summary of current ultrasound contrast technology and then review the latest research in the use of targeted ultrasound contrast agents.
Keywords: Angiogenesis; Atherosclerosis; Blood pool enhancement; Inflammation; Lymphatic system; Molecular imaging; Physiological systems; Reticuloendothelial system; Targeted imaging; Ultrasound contrast agents